Yunnan Baiyao (YNBY): pharmacological mechanisms, therapeutic applications, and clinical evidence - Hongjing Qian; Hongjing Qian; Wanli Zhang; Wanli Zhang; Mingzhu Zhang; Mingzhu Zhang; Sijia Ma; Sijia Ma; Manhong Zhen; Manhong Zhen; Hongbing He; Hongbing He; et al. (Frontiers in Pharmacology)
Yunnan Baiyao (YNBY) is a traditional Chinese medicine widely used in hemostasis, anti-inflammation, antibacterial, analgesia and wound healing. This article reviews the research progress on the pharmacological mechanism, clinical application and safety of YNBY in the past two decades. Through systematic analysis of clinical trials, animal experiments and mechanistic studies, YNBY has shown significant effects in reducing surgical bleeding (such as reducing blood loss in orthognathic surgery by 21.4%), accelerating wound healing (such as increasing the healing rate of diabetic ulcers by 37%), regulating inflammation (such as inhibiting the expression of IL-6/CRP in arthritis), and inhibiting bacterial virulence (such as destroying Staphylococcus aureus biofilm). Mechanistic studies have shown that YNBY acts through multiple pathways, including platelet activation, arachidonic acid metabolism regulation and autophagy regulation. However, existing studies have limitations such as inconsistent trial design and insufficient long-term safety data. This study provides a theoretical basis for optimizing the clinical application of YNBY, and points out future research directions, including the identification of active ingredients, the development of targeted delivery systems, and the development of large-scale randomized controlled trials.